2022
DOI: 10.1111/mec.16788
|View full text |Cite
|
Sign up to set email alerts
|

Genomic signals of local adaptation and hybridization in Asian white birch

Abstract: Disentangling the numerous processes that affect patterns of genome‐wide diversity in widespread tree species has important implications for taxonomy, conservation, and forestry. Here, we investigate the population genomic structure of Asian white birch (Betula platyphylla) in China and seek to explain it in terms of hybridization, demography and adaptation. We generate whole genome sequence data from 83 individuals across the species range in China. Combining this with an existing data set for 79 European and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Moreover, genetic grouping at K = 3 and PCA plots both indicated that the East and South clusters are mixed with the North, Central or West clusters ( Fig. 2 A and D), indicating they are likely introgressed rather than divergent lineages, as for example in white birch ( Nocchi et al., 2023 ), although more evidence is needed. In the East and South clusters located in the HM, which is characterized by deeply dissected landscapes and has created complex genetic structure, geological isolation and hybridization are likely the main factors that have shaped genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, genetic grouping at K = 3 and PCA plots both indicated that the East and South clusters are mixed with the North, Central or West clusters ( Fig. 2 A and D), indicating they are likely introgressed rather than divergent lineages, as for example in white birch ( Nocchi et al., 2023 ), although more evidence is needed. In the East and South clusters located in the HM, which is characterized by deeply dissected landscapes and has created complex genetic structure, geological isolation and hybridization are likely the main factors that have shaped genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This region has been suggested to be a site of dynamic flora as numerous species are presently becoming reproductively isolated ( Wu et al., 2022 ). For example, hybridization and young speciation are frequently observed among not only speciose alpine herbs or shrubs, including Gentiana ( Fu et al., 2020 , 2022a ), Saxifraga ( Ebersbach et al., 2020 ) and Rhododendron ( Zheng et al., 2021 ; Ma et al., 2022 ), but also woody species such as Pterocarya ( Wang et al., 2023 ), Populus ( Li et al., 2023 ) and Betula ( Nocchi et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of population structure is consistent with previous studies in East Asia ( Wu and Wu, 1996 ; Qiu et al ., 2011 , 2017 ; Chen et al ., 2015 ; Ma et al ., 2015 ; Cao et al ., 2016 , 2020 ; Wei et al ., 2016 ). The two genetic clusters within the Sino-Himalayan Forest subkingdom seem to mirror the similar phylogeographic break in many other species ( Meng et al ., 2015 ; Yang et al ., 2017 ; Luo et al ., 2018 ; Wang et al ., 2019 ; Nocchi et al , 2023 ). The level of genetic differentiation among P. macroptera populations is higher than that in other closely related wingnut taxa ( P. stenoptera : 0.067) ( Li et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 and SI Appendix, Table S1). These datasets included exclusively natural populations and ranged from closely related sister species known to hybridize (50) to species separated by up to 160 million years of evolution (Fig. 1B).…”
Section: Datasets Assembly and Filteringmentioning
confidence: 99%